Inhibition of the mRNA-Binding Protein IGF2BP1 Suppresses Proliferation and Sensitizes Neuroblastoma Cells to Chemotherapeutic Agents - Biegel, Jason M.; Dhamdhere, Mayura; Gao, Shuang; Gowda, Chethana P.; Kawasawa, Yuka Imamura; Spiegelman, Vladimir S. (Frontiers in Oncology, 2021)
Gain at chromosome 17q21 in neuroblastoma and is associated with a poor prognosis, independent of MYCN amplification status. Several potential proto-oncogenes have been identified in this region, one of them - insulin-like growth-factor-2 mRNA binding protein (IGF2BP1) – is expressed at high levels in stage 4 tumors, and associated with overall lower patient survival. Here, we demonstrate that down-regulation of IGF2BP1 activity, either by transcript silencing or chemical inhibition, suppresses neuroblastoma cell growth. Furthermore, the combination of IGF2BP1 inhibition along with commonly used chemotherapeutics that broadly affect DNA synthesis, or cyclin-dependent kinase (CDK) inhibitors that disrupt signal transduction, have a synergistic effect on the suppression of neuroblastoma cell proliferation.